Literature Review of Curriculum Management Model Development of Addiction Science Study Program - Erna Setiyaningrum; Ismet Basuki; Sri Setyowati (Studies in Learning and Teaching, 2022)
Drug abuse among college students is a worrying problem and threatens the survival of the nation. At Health University (HU) of Healthy Building Indonesian National Nurses Association (INNA) Mojokerto East Java, drug education is also provided for nursing students. Therefore, the researcher conducted a literature review regarding the development of a curriculum management model for the addiction study program at HU INNA Mojokerto, East Java. This is useful as a foundation for researchers to establish schools with addiction science with the specialization of nurses and addiction counsellors who can later assist in treating victims of drug addiction and providing counselling services to drug addicts. The results shows that as for the components of mastery of knowledge, special work abilities, and authority and responsibility, it refers to the level 6 INQF in the field of addiction treatment that has been agreed upon by the INQF Directorate General of Higher Education drafting team involving the INNA. The implication of this research is to prepare the curriculum with the aim of providing guidelines for institutions providing addiction care services education in Indonesia. Content of addiction nurse management materials: addiction case management, recovery management, addiction care service management.